Changing Rates of Goals of Care Designations in Patients With Advanced Pancreatic Cancer During a Multifactorial Advanced Care Planning Initiative: A Real-World Evidence Study. Issue 6 (2nd June 2022) - Anaka, Matthew; Lee, Minji; Lim, Elisa; Ghosh, Sunita; Cheung, Winson Y.; Spratlin, Jennifer
Abstract : PURPOSE: Goals of care (GoC) designations are an important part of advanced care planning (ACP) for patients with incurable cancers. Studies of outpatient oncology records show that most patients do not have GoC documented. We performed a retrospective analysis of changes in GoC designations in patients with advanced pancreatic cancer in Northern Alberta, Canada, during a system-wide ACP quality improvement initiative. METHODS: Four hundred seventy-one patients with newly diagnosis of advanced, non-neuroendocrine pancreatic cancer between 2010 and 2015 in Northern Alberta, Canada, were included. The ACP initiation launched April 2014, and included educational materials for patients and families, and a coded system of GoC designations describing care philosophies and preferences for resuscitation and medical interventions. Data sources included the Alberta Cancer Registry and oncology-specific electronic medical records. RESULTS: 25.5% of patients had a documented GoC, which increased over the study period (Mantel-Haenszel test-of-trend P < .001; increased from 7.8% in 2010 to 50.0% in 2015). GoC designations occurred later in patients who received palliative chemotherapy versus those who did not (median 130 days from diagnosis [95% CI, 76.019 to 183.981] v 36 days [95% CI, 28.107 to 43.893]; P < .001), and coincided with the end of treatment (median 4.5 days from last treatment). 64.8% of GoC designations were documented by palliative care physicians, but the proportion documented by medical oncologists increased with time (Mantel-Haenszel test-of-trend P = .020; increased from 0% in 2010 to 52.1% in 2015). CONCLUSION: GoC documentation increased in the outpatient records of patients with advanced pancreatic cancer during the system-wide, multifactorial ACP initiative. GoC documentation by medical oncologists also increased. These data provide real-world evidence supporting the impact of a specific ACP initiative to improve rates of GoC designation in patients with advanced cancer. Abstract :